LEGAL STUDIES COURSES ENTREPRENEURSHIP, LEADERSHIP AND PROPAGATION IN SHAPING INTERESTS AND DEVELOPMENT PATTERNS OF STUDENT ENTREPRENEURIAL LEGAL STUDIES - Aryani Witasari; Masrus Ridwan; Siti Rodhiyah Dwi Istinah (UNISSULA, 2019)
To overcome the labor force in our country continues to increase from year to year, the government has transformed the world of education by requiring entrepreneurship education at several universities, including in Faculty of Law, Islam Sultan Agung IslamicUniversity. Entrepreneurship courses, Propagation leadership and has even become one of the special compulsory curricula. The goal is that students thinking paradigm change, ie of thinking worker became the creator of the work. The mindset of the student is stilldominated by the desire to be employees. Lack of motivation and interest in entrepreneurship is thought to be one cause their mindset has not changed. Conditions were not much different there as well may occur and are experienced by students of legalscience education program undergraduate Sultan Agung Islamic University. Hopefully, the results of this study could also be input for the faculty of law, in particular lecturer entrepreneurship courses, the materials, and the learning process the eye teachingentrepreneurship suitable and appropriate for students of legal studies program undergraduate.